Caracterização de resistência a quinolonas em Salmonella enterica isoladas de materiais de origem avícola do sul do Brasil - Drescher, Guilherme (2013)
Salmonella enterica is considered an important zoonotic pathogen that can be responsible by losses in animal production, especially in poultry husbandry. Different classes of antimicrobials have been used as a prophylactic and/or therapeutic in poultry production, highlighting the quinolones, which also are indicated for human use. The wide use of these antimicrobials may contribute to the selection of microorganisms resistant to these drugs. Resistance to quinolones has been assigned to mutations in genes encoding DNA gyrase and topoisomerase IV, in addition to being associated with the presence of plasmid-mediated quinolone resistance (PMQR), especially encoded by qnr and aac(6')-Ib-cr genes. Thus, the aim of this study was to evaluate the presence of efflux pump systems involved in the resistance to quinolones using the efflux pump inhibitor carbonyl cyanide m-chlorophenylhydrazone (CCCP), and identify the presence of resistance determinants to quinolones in isolates of S. enterica from poultry-related material. For this, 36 S. enterica strains resistant to quinolones were used. The reduction of the activity of efflux pump systems was detected in 66.7% of isolates tested for nalidixic acid and ciprofloxacin with addition of CCCP. Mutation in DNA gyrase was determined by sequencing and analysis of the gyrA gene, and qnr (A, B, D and S) and aac(6')-Ib-cr genes were detected by PCR. Analysis of the gyrA gene sequences in isolates phenotypically resistant to quinolones identify the presence of mutation leading to the alteration Ser83→Phe and Asp87→Gly, Asn or Tyr in 38,9% and 22,2%, respectively. Plasmid profile analysis showed nine profiles with plasmids that ranged from ~2 kb to ~50 kb, and PMQR genes were found in 22.2% of S. enterica isolates. qnrA and qnrB genes were detected in 11.1% and 5.5% of isolates, respectively, and qnrS was found in 2.7%. None qnrD gene was found in the isolates tested. aac(6')-Ib-cr gene was detected in 8.3% of the isolates. To our knowledge, this study reports for the first time mutations in gyrA in S. Worthington from poultry, as well as this is the first report of the presence of qnrA, qnrS and aac(6')-Ib-cr in S. enterica isolated from samples related to poultry production chain in Brazil. The presence of resistance determinants to quinolones in S. enterica isolates from poultry leads to concern regarding to potential resistance selection due to the use of these antimicrobials in animal production.